2015
DOI: 10.1128/aem.01159-15
|View full text |Cite
|
Sign up to set email alerts
|

Implications of Genome-Based Discrimination between Clostridium botulinum Group I and Clostridium sporogenes Strains for Bacterial Taxonomy

Abstract: c Taxonomic classification of Clostridium botulinum is based on the production of botulinum neurotoxin (BoNT), while closely related, nontoxic organisms are classified as Clostridium sporogenes. However, this taxonomic organization does not accurately mirror phylogenetic relationships between these species. A phylogenetic reconstruction using 2,016 orthologous genes shared among strains of C. botulinum group I and C. sporogenes clearly separated these two species into discrete clades which showed ϳ93% average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
65
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(78 citation statements)
references
References 53 publications
13
65
0
Order By: Relevance
“…All but one of the C. sporogenes genomes clustered in C. botulinum Group I (lineage II), together with nine C. botulinum genomes forming a more distantly related lineage ( Figure 1A , lineage II and Supplementary Table S4). It was recently reported that C. botulinum strains CDC68016, ATCC 51387, Prevot 1662, Osaka05, and Okayama2011 were defined as C. sporogenes -like strains that may have acquired a neurotoxin gene via horizontal transfer of plasmid DNA (Weigand et al, 2015). Conversely, C. sporogenes strain CDC24533 belonging to lineage I is a C. botulinum Group I strain that probably lost its neurotoxigenic plasmid (Weigand et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…All but one of the C. sporogenes genomes clustered in C. botulinum Group I (lineage II), together with nine C. botulinum genomes forming a more distantly related lineage ( Figure 1A , lineage II and Supplementary Table S4). It was recently reported that C. botulinum strains CDC68016, ATCC 51387, Prevot 1662, Osaka05, and Okayama2011 were defined as C. sporogenes -like strains that may have acquired a neurotoxin gene via horizontal transfer of plasmid DNA (Weigand et al, 2015). Conversely, C. sporogenes strain CDC24533 belonging to lineage I is a C. botulinum Group I strain that probably lost its neurotoxigenic plasmid (Weigand et al, 2015).…”
Section: Resultsmentioning
confidence: 99%
“…It was recently reported that C. botulinum strains CDC68016, ATCC 51387, Prevot 1662, Osaka05, and Okayama2011 were defined as C. sporogenes -like strains that may have acquired a neurotoxin gene via horizontal transfer of plasmid DNA (Weigand et al, 2015). Conversely, C. sporogenes strain CDC24533 belonging to lineage I is a C. botulinum Group I strain that probably lost its neurotoxigenic plasmid (Weigand et al, 2015). C. botulinum Group II strains were separated into two distinct lineages ( Figure 1B ; Supplementary Table S4).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, it is now apparent that C. sporogenes is not simply a non-toxigenic version of C. botulinum Group I [5, 7•, 49•, 50]. Core genome SNP analysis reveals two clusters, that each contain strains of non-toxigenic C. sporogenes and Group I type B, distantly located from other Group I strains (lower two clusters in Figure 2, panel a).…”
Section: Genomic Diversity Of Clostridium Botulinum Group Imentioning
confidence: 99%
“…We are currently in the process of screening clade II C. sporogenes PA 3679 isolates for C. sporogenes clade-specific genes identified by Weigand et al (24). A thorough genomic comparison between clade II isolates of C. sporogenes PA 3679 and group I C. botulinum strains to highlight the gene content differences between these organisms, especially genes that may be involved in increased spore heat resistance, is also in progress.…”
Section: Discussionmentioning
confidence: 99%